INTEGRASI PROGRAM MADRASAH DINIYAH DAN KURIKULUM FORMAL DALAM MENUMBUHKAN KARAKTER DI SMP NEGERI 2 JOGOROTO JOMBANG - Ida Inayawati; Laily Masruroh (JOURNAL SAINS STUDENT RESEARCH, 2025)
. This article integrates the Diniyah Madrasah Program and Formal Curriculum in Cultivating Character at SMP Negeri 2 Jogoroto Jombang. This approach uses a qualitative approach with a descriptive type of research. Data collection techniques are carried out using observation, interview, and documentation methods. The results of the study indicate that: 1) The diniyah madrasah program at SMP Negeri 2 Jogoroto Jombang runs very well and is structured. 2) The formal curriculum at SMP Negeri 2 Jogoroto Jombang runs very well and is scheduled. 3) The integration of the diniyah madrasah program and the formal curriculum at SMP Negeri 2 Jogoroto Jombang can be seen from the alignment of the same PAI lesson materials and objectives. 4) Supporting factors for the diniyah madrasah program and curriculum in cultivating character are the existence of training and development for supervising teachers, the existence of religious learning that is connected to diniyah, the use of callphones during learning according to the teacher’s intructions, the inhibiting factors are the diversity of student backgrounds in understanding religious knowledge, and the diverse interests of students in learning.